2003
DOI: 10.1021/bm0255948
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Bombyx mori Silk Fibroin in the Calcium Nitrate Tetrahydrate−Methanol System and Aspects of Wet Spinning of Fibroin Solution

Abstract: There are still several problems associated with the spinning of dialyzed silk fibroin solutions. In this work some of these problems have been examined. The calcium nitrate tetrahydrate-methanol system was used to dissolve the silk fibroin. A compositional phase diagram was constructed at various concentrations of the solvent system. Regenerated fibroin powders from undialyzed fibroin solution in several coagulants showed different conformations. Regenerated powders from several coagulants except methanol and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
82
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 23 publications
6
82
0
Order By: Relevance
“…On 70% (v/v) ethanol treatment the Tg peak shifts to 105.878C. Due to presence of b-sheet conformation in the ethanol treated films, there was absence of any exothermic peaks as previously seen in case of untreated amorphous films (Ha et al, 2003). It was noteworthy that with ethanol treatment there was subsequent increase in the degradation onset temperature from 142 to 1748C (increase by 328C).…”
Section: Differential Scanning Calorimetrysupporting
confidence: 53%
“…On 70% (v/v) ethanol treatment the Tg peak shifts to 105.878C. Due to presence of b-sheet conformation in the ethanol treated films, there was absence of any exothermic peaks as previously seen in case of untreated amorphous films (Ha et al, 2003). It was noteworthy that with ethanol treatment there was subsequent increase in the degradation onset temperature from 142 to 1748C (increase by 328C).…”
Section: Differential Scanning Calorimetrysupporting
confidence: 53%
“…With the effect of hydrophobic interaction, Ca 2+ promotes the formation of the -sheet construction and results in shorter gelation times for the Ap-SF solution. However, higher concentrations of Ca 2+ generate a large number of binding ligands between Ca 2+ and Ap-SF due to that the oxygen atoms of the carbonyl groups in the peptide bonds of fibroin form coordination bonds with calcium ions, and the water molecules act either as a swelling agent for the silk fibroin or as components of the coordination bonds [34,35], which interferes with the aggregation and the formation of the -sheet structure of Ap-SF and even completes the solvation sheath of the ions, resulting in dissolution of the silk fibroin. This supports the observation that dense salts of Ca 2+ , e.g., Ca(NO 3 ) 2 , could be used to dissolve Ap-SF silk fiber [15,17], and the solution obtained before dialysis for removing the ions is quite stable and will not become denatured or form a gel.…”
Section: Gelation Time Of the Ap-sf Solutionmentioning
confidence: 99%
“…The conformational characteristics of the films are influenced by many factors such as the concentration of the solution, the type of solvent, and the drying temperature [16]. The secondary structural characteristics of fibroin can be influenced by low dielectric organic solvents that convert random coils of silk fibroin into a β-sheet conformation [17][18][19][20]. It was reported that methanol had improved the mechanical properties of silk fibroin film.…”
Section: Introductionmentioning
confidence: 99%